2001
DOI: 10.1034/j.1600-0722.2001.00069.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental fear in sexually abused women

Abstract: The aim of the present study was to investigate dental fear in women who have been exposed to different kinds of sexual abuse. In a cross-sectional questionnaire study, 99 sexually abused women were divided into three groups: one group who reported having been exposed to sexual touching (ST); one group who reported intercourse (IC); and one group who reported sexual abuse involving oral penetration (OP). The mean score on dental fear assessments was significantly higher for all groups than for Norwegian women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
81
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(93 citation statements)
references
References 25 publications
7
81
0
1
Order By: Relevance
“…83 Willumsen reported that 75% of women who have reported abuse that included oral penetration had high levels of dental fear. 22,83 The ability of these individuals to accept minor or major discomfort associated with instru ments in the mouth was reduced and feeling unable to breathe and/or severe gagging or choking interfering with treatment delivery were increased. 71 It is also important to note that men who have experienced CSA are more likely than women to have experienced abuse involving oral sex.…”
Section: Dental Anxietymentioning
confidence: 99%
See 3 more Smart Citations
“…83 Willumsen reported that 75% of women who have reported abuse that included oral penetration had high levels of dental fear. 22,83 The ability of these individuals to accept minor or major discomfort associated with instru ments in the mouth was reduced and feeling unable to breathe and/or severe gagging or choking interfering with treatment delivery were increased. 71 It is also important to note that men who have experienced CSA are more likely than women to have experienced abuse involving oral sex.…”
Section: Dental Anxietymentioning
confidence: 99%
“…81 Parallels have been drawn between the long-term effects of CSA and the spe cifi c factors that lead to increased stress being in a horizontal position, feeling claustrophobic, being alone with some one more powerful, loss of control and anticipating or experiencing pain. 71,83,84 Additionally, the oral cavity is a frequent site of CSA 85 and while visible signs of CSA involving the oral cavity are rare, 86 their emotional significance has a long lasting impact. 83 Willumsen reported that 75% of women who have reported abuse that included oral penetration had high levels of dental fear.…”
Section: Dental Anxietymentioning
confidence: 99%
See 2 more Smart Citations
“…[30][31][32] There is also an observed association between dental anxiety and having been the victim of past sexual abuse. 33,34 All these various factors might be indirectly or directly implicated in a patient's dental-related anxiety and should be determined when appropriate.…”
Section: The Nature Of Dental Fearmentioning
confidence: 99%